Model Creative Problem Solving Terintegrasi Teknologi dalam Pembelajaran Matematika: Sebuah Pola, Peluang, dan Tantangan - Imam Nursahid; Agus Maman Abadi; Wahyu Setyaningrum (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
The implementation of the Creative Problem Solving (CPS) learning model integrated with technology has significantly transformed mathematics education. This innovation introduces new instructional patterns that present both opportunities and challenges, requiring educational institutions to adapt in order to maximize benefits and address emerging constraints. This study aims to examine the outcomes of technology based CPS in mathematics learning by mapping integration patterns, identifying implementation opportunities, and analyzing the challenges encountered. This research employed a Systematic Literature Review (SLR) method. The article search was conducted on October 15, 2025, across two major databases, Google Scholar and Scopus, using Harzing’s Publish or Perish. The search strategy combined the keyword “Creative Problem Solving” with technology-related terms in mathematics education and applied Boolean operators. Based on the selection and screening process, 27 articles met the inclusion criteria. The findings reveal two dominant patterns of CPS technology integration: web based and Learning Management System platforms such as Google Classroom and Google Sites (n=8), and mathematical visualization platforms such as GeoGebra and Desmos (n=6). Twenty-five of the 27 studies focused primarily on improving mathematical cognitive abilities, particularly creative thinking and problem-solving skills, along with several affective aspects. The results indicate that integrating CPS with technology contributes positively to mathematics learning outcomes. However, key challenges remain, including disparities in digital readiness among teachers and students, limited access to devices and stable internet connectivity, and the potential for increased cognitive load. This review maps CPS technology integration architectures and identifies prerequisites for effective implementation in mathematics education.